The Relationship Of Registration Waiting Time With Patient Satisfaction In Outstanding Registration In Grandmed Hospital Lubuk Pakam - Sri Melda Br Bangun; Aya Sofia Diaz; Latifah Hanum (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Patient satisfaction is the focus of hospital services, where competition between hospitals is common nowadays so that patients who are satisfied with the services they provide will come back. this is an assessment given to patients on health services that are obtained as expected starting from reception until the patient goes home (Sitorus. 2021). Satisfaction will have an impact on improving health services in the future so that it remains low even though there are many hospitals that are growing. This type of research is an analytic survey with a cross sectional design. The population used was all 96 pulmonary polyclinic patients with a sample of 32 people using purposive sampling technique. The results showed that there was a relationship between patient satisfaction on tangible dimensions (0.000 < 0.005), reliability (0.000 < 0.005), responsiveness (0.490 > 0.005), assurance (0.281 > 0.005), empathy (0.000 < 0.005) and waiting time for registration. The conclusion of this study is the relationship between waiting time for registration and patient satisfaction in the outpatient registration section of Grandmed Lubuk Pakam Hospital